2023
DOI: 10.1002/aelm.202300559
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Properties Investigation of AgNWs‐PEDOT:PSS Based Transparent Conductive Electrode for Ultraflexible Organic Photodetector Applications

Jostin Vinroy Dcosta,
Daniel Ochoa,
Sébastien Sanaur

Abstract: In this work, the optoelectrical, mechanical, and material properties of silver nanowires/poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (AgNWs‐PEDOT:PSS) hybrid electrode, solution processed on 5 µm parylene‐C substrate for ultraflexible organic photodetector (OPD) applications, are investigated. The fabricated transparent conductive hybrid electrode exhibits low sheet resistance (Rs) of 27 Ω Sq.−1 and shows an average optical transmission of 90% in the visible spectrum. Besides the comparable work f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
0
0
Order By: Relevance
“…As shown in Figure e, the OPD in the spin-coated PEDOT:PSS electrode condition confirmed that J d was greatly increased from 1.62 × 10 –9 A cm –2 (before bending) to 1.33 × 10 –8 A cm –2 after 500 bending cycles, and increased to 6.70 × 10 –8 A cm –2 after 1000 bending cycles at 0 V, while the OPD in the transferred PEDOT:PSS condition was significantly improved (from 1.53 × 10 –9 A cm –2 before bending to 4.20 × 10 –9 A cm –2 after 500 bending cycles at a 0 V bias before bending and 9.44 × 10 –9 A cm –2 after 1000 bending cycles). This is because the sharper interface formed by the transferred PEDOT:PSS patch with the upper layer yielded increased mechanical robustness. , (Figure f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure e, the OPD in the spin-coated PEDOT:PSS electrode condition confirmed that J d was greatly increased from 1.62 × 10 –9 A cm –2 (before bending) to 1.33 × 10 –8 A cm –2 after 500 bending cycles, and increased to 6.70 × 10 –8 A cm –2 after 1000 bending cycles at 0 V, while the OPD in the transferred PEDOT:PSS condition was significantly improved (from 1.53 × 10 –9 A cm –2 before bending to 4.20 × 10 –9 A cm –2 after 500 bending cycles at a 0 V bias before bending and 9.44 × 10 –9 A cm –2 after 1000 bending cycles). This is because the sharper interface formed by the transferred PEDOT:PSS patch with the upper layer yielded increased mechanical robustness. , (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…This is because the sharper interface formed by the transferred PEDOT:PSS patch with the upper layer yielded increased mechanical robustness. 83,84 (Figure 6f). Based on this, the responsivity and detectivity of the spincoated PEDOT:PSS electrode-and transferred PEDOT:PSS patch-based device can be calculated (as a function of the bending cycle) using the following equations,…”
Section: Work Of Adhesion (γ A−b ) Refers To Adhesion Strength Betwee...mentioning
confidence: 99%